Análise comparativa de abordagens fuzzy AHP para segmentação de fornecedores sustentáveis com o fuzzy TOPSIS - ALMEIDA, Cléubio Ignácio de (2019)
Segmentation plays a key role in the supplier management, but it is still a field of research that has much to explore. The creation of new segmentation methods, as well as better understanding and comparison of existing methods, will lead researchers and practitioners to make decisions aligned with the development of more sustainable supply chains. The objective of this work is to perform a comparative analysis of two popular approaches of the Fuzzy AHP (Analytical Hierarchy Process), combined with Fuzzy TOPSIS (Technique for Order of Preference by Ideal Solution), and applied in the supplier segmentation matrix proposed by Rezaei and Ortt (2012). For this, two methods of sustainable suppliers segmentation were presented, which differ in the derivation of the criteria weights vector in the fuzzy AHP approach. The first one used the geometric mean method, while the second one used the extent analysis method. The result was the segmentation of suppliers into four segments of a two dimensions matrix: "supplier's sustainable capabilities", with supplier evaluation criteria based on the triple bottom-line concept; and "supplier willingness to cooperate," with criteria that lead to long-term relationship building. Finally, the methods were compared with the criteria that characterize a supplier segmentation, considering order and values of criteria weights, supplier performance, sustainable supplier segmentation matrix, and suitability to change criteria. Practical application of supplier segmentation occurred in a dairy company. The results of the work showed that the two methods reached very similar segmentation matrices, but the method that used the geometric mean was more adequate, since it had a better performance in the comparison criteria analyzed.